2019
DOI: 10.15446/revfacmed.v67n3.65741
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance trends in methicillin-resistant and methicillin-susceptible Staphylococcus aureus and Staphylococcus epidermidisisolates obtained from patients admitted to intensive care units. 2010-2015

Abstract: Introducción. La aparición y la diseminación de cepas resistentes en hospitales, principalmente en unidades de cuidado intensivo (UCI), se han convertido en un serio problema de salud pública.Objetivo. Analizar la tendencia de los fenotipos de resistencia de Staphylococcus aureus y Staphylococcus epidermidis resistentes y susceptibles a meticilina aislados en pacientes atendidos en UCI de un hospital de alta complejidad de Cartagena, Colombia, del 2010 al 2015.Materiales y métodos. Estudio analítico transversa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
1
0
0
2
Order By: Relevance
“…According to data from the Bacterial Resistance Control Group (GREBO) in Bogota, the MRSA rate in pediatric settings ranged from 34.3% to 46.1% in 2011 (26), 34.8%-42.1% in 2015 (30) and increased to 46.2%-49.2% in 2021 (31). Montes et al also found MRSA rates between 40% and 50% in pediatric isolates from 2009 to 2017, which aligns with the stable 45% MRSA rates in adults reported by Castro-Orozco et al during a similar time period (32,33).…”
Section: Trends In Oxacillin Resistancesupporting
confidence: 75%
“…According to data from the Bacterial Resistance Control Group (GREBO) in Bogota, the MRSA rate in pediatric settings ranged from 34.3% to 46.1% in 2011 (26), 34.8%-42.1% in 2015 (30) and increased to 46.2%-49.2% in 2021 (31). Montes et al also found MRSA rates between 40% and 50% in pediatric isolates from 2009 to 2017, which aligns with the stable 45% MRSA rates in adults reported by Castro-Orozco et al during a similar time period (32,33).…”
Section: Trends In Oxacillin Resistancesupporting
confidence: 75%
“…En un Hospital del Estado en Delhi, India, se realizó un estudio donde describen patrones de resistencia y consumo antibiótico en una unidad de cuidado intensivo de un tercer nivel, reportando como los aislamientos más frecuentes Klebsiella spp con 15 reportes, siendo el más prevalente, seguido de Acinetobacter con 12 reportes, seguido de E. coli con 8 reportes y dentro de los gérmenes gram positivos el 60% de todos los casos de S. aureus tienen un patrón resistencia a la meticilina, este último problema que ya se viene documentando en la región Caribe Colombiana como informa Raimundo Castro et al (10), (11) mientras que en el presente estudio se aislaron 7 reportes de Klebsiella spp, siendo el más prevalente (35%), seguido de Staphylococcus con 5 reportes (25%), seguidos de Acinetobacter, Serratia, Pseudomona con 2 reportes cada uno (10%) y por último 1 reporte de Eschericia (5%) y 1 reporte de Stenotrophomonas (5%).…”
Section: Discussionunclassified
“…Hasil ini tidak jauh berbeda dengan studi Castro-Orozco dkk yang dilakukan pengumpulan isolate ICU dari tahun 2010-2015, didapatkan angka MRSA sebesar 45,7% dan MRSE sebesar 75%. 16 Pola kepekaan patogen penyebab infeksi nosokomial di ruang perawatan ICU dari berbagai penelitian menunjukkan banyaknya bakteri yang multidrug resisten. Hal ini dapat disebabkan oleh penggunaan antibiotik yang tinggi selama perawatan di ICU.…”
Section: Pembahasanunclassified